Distribusi Benign Soft Tissue Tumor berdasarkan Gender dan Usia - Islamuddin, Tri Kurnia Ahmad; Kurniati, Yuni Prastyo (Prosiding University Research Colloquium, 2022)
Soft tissue tumor is a disorder that occurs in non-epithelial tissue including fatty tissue, fibrous tissue, neurovascular tissue and muscle tissue. This disease is more common in women than men. While the age that is often diagnosed with this lesion is found in the age range of 15-25 years and 35-54 years. This study aims to analyze whether there is an influence between gender and age with the distribution of benign soft tissue tumors. This study uses a cross sectional study with a retrospective approach. The research sample was histopathological preparations taken from 161 patients with medical record data according to the inclusion criteria. Sampling using purposive sampling technique. Data were analyzed using fisher test. Based on gender, the highest frequency of samples was female as much as 51.6%. Based on age, it was found more in the age range of 17-25 years. The results of the chi-square test of the effect of gender on the distribution of benign soft tissue tumors showed p 1.000, while the effect of age on the distribution of benign soft tissue tumors showed p 0.407. There is no significant effect between the distribution of benign soft tissue tumors on gender and age.